The Interplay of Host Lysosomes and Intracellular Pathogens - Sachdeva, Kuldeep; Sundaramurthy, Varadharajan (Frontiers in Cellular and Infection Microbiology, 2020)
Lysosomes are an integral part of the intracellular defense system against microbes. Lysosomal homeostasis in the host is adaptable and responds to conditions such as infection or nutritional deprivation. Pathogens such as Mycobacterium tuberculosis (Mtb) and Salmonella avoid lysosomal targeting by actively manipulating the host vesicular trafficking and reside in a vacuole altered from the default lysosomal trafficking. In this review, the mechanisms by which the respective pathogen containing vacuoles (PCVs) intersect with lysosomal trafficking pathways and maintain their distinctness are discussed. Despite such active inhibition of lysosomal targeting, emerging literature shows that different pathogens or pathogen derived products exhibit a global influence on the host lysosomal system. Pathogen mediated lysosomal enrichment promotes the trafficking of a sub-set of pathogens to lysosomes, indicating heterogeneity in the host-pathogen encounter. This review integrates recent advancements on the global lysosomal alterations upon infections and the host protective role of the lysosomes against these pathogens. The review also briefly discusses the heterogeneity in the lysosomal targeting of these pathogens and the possible mechanisms and consequences.